The Mapping Of Verbs In The Novel Entitled Paper Towns Into Its Translation Kota Kertas - Dewa Made, Agustawan; Komang Astiari; I Putu Eka Suardana (Outline Publisher, 2024)
This paper focuses on the translation of verbs in the novel entitled Paper Towns by John Green (2008) into its translation Kota Kertas by Angelic Zaizai by applying the Natural Semantic Metalanguage (NSM) proposed by Wierzbiecka (1996). In this paper, were found 5 verbs to be analyzed by the NSM theory. They are; reminded, kissed, laughing, hit, and trying. The NSM used to distinguish and analyzed the differences of the lexicon from the source language into the target language.